2005
DOI: 10.1136/ard.2003.019984
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuous synovial lymphatic capillaries in juvenile idiopathic arthritis synovitis with rice bodies

Abstract: T he paper of Mohr discussing the development of rice bodies with apatite crystals in fibrinous debris synovitis in rheumatoid arthritis 1 prompted us to describe our recent morphological findings.During synovectomy in a 33 year old woman with a longlasting systemic form of juvenile idiopathic arthritis (JIA) a large number of rice bodies and numerous synovial villi connected to the synovial membrane (SM) by very thin stalks were visible in the joint space (JS). Light microscopy of paraffin sections showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…A generalized abnormality in capillary function (an increase in capillary filtration rate) and some obstruction of lymphatic clearance are associated with rheumatoid arthritis 10,11 . Microscopic changes of postcapillary venules were also found in RA, 12,13 and structural changes of lymphatic vessels in synovial membrane were observed in RA and juvenile idiopathic arthritis 14–16 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A generalized abnormality in capillary function (an increase in capillary filtration rate) and some obstruction of lymphatic clearance are associated with rheumatoid arthritis 10,11 . Microscopic changes of postcapillary venules were also found in RA, 12,13 and structural changes of lymphatic vessels in synovial membrane were observed in RA and juvenile idiopathic arthritis 14–16 …”
mentioning
confidence: 99%
“…10,11 Microscopic changes of postcapillary venules were also found in RA, 12,13 and structural changes of lymphatic vessels in synovial membrane were observed in RA and juvenile idiopathic arthritis. [14][15][16] Adjuvant arthritis, an experimentally induced inflammatory disorder in rats, bears some features of rheumatoid arthritis. In both diseases edema and inflammation appear in synovial joints.…”
mentioning
confidence: 99%
“…Istnieją doniesienia o namnażaniu się naczyń limfatycznych błony maziowej u pacjentów z RZS po leczeniu przeciwciałami anty-TNF [5]. W 2005 r. opisano wyraźnie widoczne włosowate naczynia limfatyczne w błonie ma ziowej [28]. Wilkinson i Edwards [7] dostarczyli zdjęcia naczyń limfatycznych zlokalizowanych w pobliżu głęboko położonych tętniczek i małych naczyń żylnych ludzkiej błony maziowej przy użyciu lektyny z kolcolistu zachodniego (lectin Ulex europaeus agglutinin I -UEAAI); jednak przy zastosowaniu tej metody u pacjentów z RZS badane próbki nie wykazały obecności naczyń limfatycznych.…”
Section: The Authors Declare No Conflict Of Interestunclassified
“…treatment with anti-TNF antibody [5]. Conspicuous LC were described in synovial membrane in 2005 [28]. Wilkinson and Edwards [7] provided visualisation of lymphatic vessels situated in the proximity of deep arterioles and venules of the human synovial membrane using lectin Ulex europaeus agglutinin I (UEAI); however, using this method in RA patients, the samples did not show any lymphatic vessels.…”
Section: R Ry Yc C 3 3 Błona Maziowa Z Przerośniętą Warstwą Kommentioning
confidence: 99%
“…In recent years, B cells have been found to play a critical role in the pathology of RA and thus provide a new target for treatment. , B cells are primarily involved in propagating the autoimmune response in rheumatoid arthritis through autoantibody generation, T cell and myeloid cell activation, and pro-inflammatory cytokine production. , In addition to promoting immune activation and inflammation, B cells also appear to play a role in promoting lymphatic dysfunction that, in turn, exacerbates joint inflammation. Studies over the last two decades have demonstrated a range of structural and functional changes to the synovial and prenodal joint-draining lymphatics in experimental inflammatory arthritis, osteoarthritic (OA) mouse models, and humans with arthritis. These experiments collectively report disease severity-related changes in (1) the density and size of lymphatic vessels within the synovium, (2) the composition of joint-draining lymph, (3) the drainage kinetics of joint-draining lymph, and (4) the morphology of the joint-draining lymph node (jdLN).…”
Section: Introductionmentioning
confidence: 99%